The Argument for Choosing State's Judicial System or a "Private" Outsourced Resolution of Disputes: a Practising Attorney's Point of View - Sladič, Jorg (LeXonomica, 2018)
Terms such as arbitration, mediation, conciliation and alternative dispute resolution (ADR) are nowadays standard terms in any classroom textbook on civil procedure. Legal scholars enumerated and assessed in depth the advantages and disadvantages of any type of outsourced dispute resolution. However, a number of legal writers still fail to enumerate the exact differences in course of events and all of the trade-offs that a party will have when deciding to resolve the dispute using an outsourced dispute resolution. Clearly the costs, the celerity and the flexibility are important issues. However, the decision is not influenced solely by legal arguments. This paper will mention some typical Slovenian issues in an assessment of the choice of dispute resolution. If parties want to continue to remain in good terms after the dispute, then an outsourced dispute resolution is highly recommended. Judicial rulings are to binary; one party wins, one loses.